Vitrine de papel: as mulheres no periódico paraibano O Publicador (1864-1869) - Ladislau, Aldenize da Silva (2022)
The dissertation intended to identify the presence of women in the newspaper O Publicador. We found a variety of publications and a diversity of female figures in this journal who, in some cases, signed published articles and, in others, were the subject of the reported subject. These women carried out different activities, but experienced very similar realities with regard to patriarchal discourses, which represented them as inferior beings in many circumstances because they were female. For this research, we chose to work with all editions of O Publicador available in the Hemeroteca Digital, covering the years between 1864 and 1869. This newspaper circulated in the Province of Parahyba do Norte, daily, during the second half of the 19th century. In addition to being our main source, it is also configured as an object of study, since better understanding the journal's configuration allowed us to know the graphic and editorial elements, in which we find the presence and representations of women. We also use Cultural History, Women's History and the Perspective of Gender, Representation and Experience Studies as a theoretical-methodological arsenal to understand the trajectories of a group of women - who were in conditions of enslavement, abolitionists, actresses and teachers. This research is located in the area of History and Historical Culture, following the research line History and Regionalities. Thus, it was intended to know, above all, which social spaces this female audience circulated from the understanding of their historical time and what kind of conflicts were generated by their experiences. We conclude that through this research we were able to approach the ways in which the presence of women occurred among the sections of the newspaper O Publicador, where the participation of women in this newspaper, in particular, is marked by representations and supply of labor for the work.